Adapting Tradition to Faith: The Transformation of Maccera Tasi' in Bonepute Village amid Islamic Influence - Ibnu Azka; Fathur Baldan Haramain (Indigenous Southeast Asian and Ethnic Studies, 2025)
This study examines the transformation of the Maccera’ Tasi tradition in Bonepute, Luwu Regency, and the role of Islamic preaching in shaping community religious awareness. Using qualitative methods that combine ethnographic and phenomenological approaches, the research investigates how Islamic values have influenced the evolution of this coastal ritual. Data were gathered through interviews, participant observation, and document analysis, focusing on the perspectives of religious leaders, traditional elders, community members, and preachers. Findings indicate that Maccera’ Tasi has shifted from rituals rooted in animist practices to forms more consistent with Islamic cultural norms. This transformation has been guided by da’wah efforts, particularly through persuasive preaching and cultural engagement, which reinterpret the ritual’s meanings in line with Islamic teachings while fostering deeper religious consciousness. The study highlights the significance of contextual preaching strategies that respect local traditions while gradually aligning them with Islamic principles. It also emphasizes the value of collaboration between religious scholars and cultural practitioners to maintain the continuity of cultural heritage within an Islamic framework. Ultimately, the research demonstrates how local customs and Islamic values can be harmonized, strengthening both cultural identity and religious life.